Loneliness Among African International Students at Portuguese Universities - Neto, Félix (Journal of International Students, 2021)
International students constitute an important sojourner group. This study examined the levels and predictors of loneliness among international students. The sample included 188 Angolan, 210 Cape Verdean, and 221 domestic college students who attended Portuguese institutions of higher education. The relative strengths of background and acculturation factors in loneliness, as an indicator of psychological adaptation, were explored. Results showed that international students reported greater levels of loneliness than native-born students. As expected, results showed that students who reported poorer financial situation, greater perceived discrimination, and lower home culture and host culture acculturation orientation scores reported higher loneliness. In addition, using hierarchical regression analyses, current findings suggest that the most significant predictors of loneliness for international students were financial situation, perceived discrimination, and orientation to heritage culture. Implications of these results for reducing loneliness of international students are discussed.